Leveraging Islamic Economic To Alleviate Poverty In Indonesia : A Promising Pathway - Syahrir, Dimas Kenn; wahyudi, ickhsanto; Yunan, Zuhairan Yunmi; Rahmawati, Rahmawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2023)
This empirical study explores the relationship between Islamic banking development, social justice promotion, and poverty reduction in Indonesia, using annual time series data from 1991 to 2021.. Methodology/approach The analysis encompasses unit root tests, Johansen cointegration tests, and Vector Error Correction Models (VECM) to assess short and long-term causality among the variables. The results provide robust evidence that expanding Islamic financial institutions and increasing spending on Islamic philanthropy significantly contribute to reducing national poverty levels over both the short and long-run. Islamic finance, characterized by equity-based principles, facilitates financial access for marginalized groups, while instruments of Islamic philanthropy such as zakat and sadaqah directly assist the disadvantaged, enabling pathways out of poverty. Findings – The findings underscore the potential of Islamic economics to foster equitable, inclusive, and sustainable growth, validating the need for policy support to harness its impact